The Anatomy of the Memory Systems: An Overview of Recent Developments - Sukardi, Elias (Faculty of Psychology, Universitas Surabaya, 2001)
Results of recent studies indicate that different parts of the brain, such as the hippocampus and related structures, the striatum, the cerebellum, the amygdala, and many other locations in the brain are involved in storing particular types of information. This overview dwells into the underlying mechanisms of retention of memory which seems to be universal, featuring the involvement of calcium ions with its unique ability to couple electrical activity directly with longterm changes in the brain. Hasil-hasil studi mutakhir menunjukkan bahwa berbagai lokasi di otak seperti hippokampus dan struktur-struktur terkait, striatum, serebelum, amigdala, dan banyak lokasi lain di otak berperan dalam penyimpanan jenis-jenis tertentu ingatan. Telaah pustaka ini berupaya memahami mekanisme yang mendasari penyimpanan ingatan yang tampaknya universal, yang menunjukkan keterlibatan ion-ion kalsium dengan kemampuan uniknya untuk memadukan aktivitas elektrik secara langsung dengan perubahan-perubahan jangka panjang dalam otak.